PENGARUH LATIHAN SINGLE MULTIPLE JUMP DAN KNEE TUCK JUMP TERHADAP KETERAMPILAN LONG PASS PADA SISWA SEKOLAH SEPAKBOLA NUSANTARA USIA 15-17 TAHUN KOTA MALANG - Hafidz Gusdiyanto; Asim Asim; Fahrial Amiq (Fakultas Ilmu Keolahragaan UM)
ABSTRACT: Nusantara soccer school 15-17 years old Malang city have a problem in soccer basic technique, it is long pass skill. The purpose of this research is to know the influence exercise of single multiple jump and exercise of knee tuck jump to long pass skill in Nusantara soccer school 15-17 years old Malang city.This research using experiment research matching pretest-posttest comparison group design with subject 22 student. Based from F count 4,70 > F table 4,35 for exercise of single multiple jump, while F count 0,842 < F table 4,35 for exercise of knee tuck jump. The comparison from two excercises can be obtained F count 12,29 > F table 4,35. Based on the research can be concluded that exercise of single multiple jump give influence better than excersie of knee tuck jump.Keywords: single multiple jump, knee tuck jump, long pass.